Delay in seeking diagnosis and treatment among women with breast cancer - Norsa'adah, Bachok (Pusat Pengajian Sains Perubatan, 2012)
Breast cancer is the leading cancer that causes mortality among women in Malaysia. Delay in its diagnosis and treatment has major implications on the patients' prognosis and survival. The objectives of this study were to identify the magnitude of delay in consultation, diagnosis and initiation of treatment; and its associated factors among women with breast cancer. This study was a combination of quantitative and qualitative methods. The quantitative study was a retrospective cohort. Respondents were histo-pathologically diagnosed breast cancer patients who were registered at various medical centres in the year 2005-2007. Validated questionnaires were used to interview respondents. The qualitative study was using an in-depth interview. It was carried out in the East Coast and 12 volunteers were selected. A total of 328 respondents were included in the quantitative study. The mean (SD) age was 47.9 (9.4) years. The majority of respondents were Malays who had low a socio-economic status. The median time for first doctor consultation was 2 months, diagnosis 5.5 months and initiation of treatment 2.4 weeks. The rate of consultation delay more than a month was 66.8%, diagnosis delay more than three months was 73.2% and treatment delay more than a month was 27.4%. The significant factors associated with diagnosis delay were the number of children, grossly swollen breast, self-detected symptom, first doctor's inappropriate action, non-cancer interpretation, low level of fear and negative attitude to treatment. While factors associated with treatment delay were pregnancy, taking complementary alternative medicine, initially refusing mastectomy and having lumpectomy prior the definitive treatment. The reasons for delay were strengthened by the qualitative study. The identified themes were lack of knowledge, fear, beliefs in complementary alternative medicine, sanction by others, barriers, denial, attitude of wait and see and weakness of health care services system. This study found that delays in diagnosis and consultation were serious problems. Decision on health seeking behaviour was influenced by a complex interaction of socio-demographic, clinical, cognitive, practices, environmental, beliefs, cultural and psycho-social factors. A comprehensive intervention is suggested in order to detect, diagnose and treat breast cancer early before the tumour enlarges and spreads to lymph nodes and metastasis.